2007
DOI: 10.1016/j.jmb.2007.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Folding Amphipathic Helices Into Membranes: Amphiphilicity Trumps Hydrophobicity

Abstract: High amphiphilicity is a hallmark of interfacial helices in membrane proteins and membrane-active peptides, such as toxins and antimicrobial peptides. Although there is general agreement that amphiphilicity is important for membrane-interface binding, an unanswered question is its importance relative to simple hydrophobicity-driven partitioning. We have examined this fundamental question using measurements of the interfacial partitioning of a family of seventeenresidue amidated-acetylated peptides into both ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
147
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(157 citation statements)
references
References 55 publications
10
147
0
Order By: Relevance
“…The measurements of the interfacial partitioning of a family of 17-residue amidated-acetylated peptides into both neutral and anionic lipid vesicles showed that peptide helicity in water and interface increased linearly with hydrophobic moment, as did the favorable peptide partitioning free energy. This results demonstrates that helical amphipathicity plays more significant roles in interfacial binding than hydrophobicity does (Fernandez-Vidal et al, 2007).…”
Section: Amphipathicity and Hydrophobic Momentmentioning
confidence: 79%
See 1 more Smart Citation
“…The measurements of the interfacial partitioning of a family of 17-residue amidated-acetylated peptides into both neutral and anionic lipid vesicles showed that peptide helicity in water and interface increased linearly with hydrophobic moment, as did the favorable peptide partitioning free energy. This results demonstrates that helical amphipathicity plays more significant roles in interfacial binding than hydrophobicity does (Fernandez-Vidal et al, 2007).…”
Section: Amphipathicity and Hydrophobic Momentmentioning
confidence: 79%
“…Several studies have shown that on the angle of helix content the mean hydrophobic moment is a more important factor affecting antimicrobial activity than hydrophobicity (Pathak et al, 1995;Fernandez-Vidal et al, 2007). The measurements of the interfacial partitioning of a family of 17-residue amidated-acetylated peptides into both neutral and anionic lipid vesicles showed that peptide helicity in water and interface increased linearly with hydrophobic moment, as did the favorable peptide partitioning free energy.…”
Section: Amphipathicity and Hydrophobic Momentmentioning
confidence: 99%
“…SecY/Sec61 (50), Tom40 (51), and Toc75 (52)). The occurrence and importance of amphipathic helices in membrane proteins have been pointed out previously (53).…”
Section: Discussionmentioning
confidence: 93%
“…Despite a superficial similarity between pHLIP and amphiphatic peptides, insertion events appear to be driven by different mechanisms. Amphiphatic peptides form ␣-helices on the surfaces of bilayers (25). As with any anisotropic inclusions they occupy only one leaflet of a bilayer and induce distortion, which increases with peptide concentration and finally results in peptide aggregation and cooperative peptide insertion into the membrane, relieving the distortion and accompanied by the formation of a pore (26).…”
Section: (For 37°c) (B)mentioning
confidence: 99%